2008
DOI: 10.1088/0957-0233/19/7/075602
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic investigation of volatile compounds produced during thermal and radiofrequency bipolar cautery on porcine liver

Abstract: The potential risks associated with the emission of by-products emitted by surgical cautery are of concern. Various investigations—mostly based on gas chromatography—have been performed to analyse the so-called surgical smoke but controversies remain in terms of composition and concentrations of compounds present in the smoke and hence the associated risk to human health. This quantitative model study uses for the first time CO2-laser-based photoacoustic spectroscopy and focuses on the analysis of volatile org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 20 publications
(22 reference statements)
0
7
0
Order By: Relevance
“…Further similar studies at this stage are in our opinion not only unnecessary but also unethical. Ongoing studies of our group are currently trying to answer the open questions with a modified experimental set-up based on the experience of this pilot study [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Further similar studies at this stage are in our opinion not only unnecessary but also unethical. Ongoing studies of our group are currently trying to answer the open questions with a modified experimental set-up based on the experience of this pilot study [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…First, the smoke composition and quantity depends largely on the combusted tissue and the employed instrument [ 4 , 11 ]. Hensman et al produced surgical smoke in their in vitro study on porcine liver, while Hollmann et al sampled gas emission during open reduction mammoplasty, both using conventional electrocautery [ 5 , 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[181]. Ray et al reported a quantitative model study where they first used laser CO 2 LPAS and focused on analyzing VOCs produced thermal and radiofrequency bipolar cautery on porcine liver [184]. They detected carbon dioxide, water vapor, ammonia, ethanol and methanol in the ppm to sub-ppm range and molar fractions, and the concentrations of methanol and ethanol differed between the two cautery devices employed.…”
Section: Lpas In Surgical Smoke Gases Detectionmentioning
confidence: 99%